The Effect of China's Monetary Policy on Financial Constraints of New Energy Vehicle Companies -- Panel Regression Model based on the SA Index and LPR - Wang, Hengnuo (Transactions on Economics, Business and Management Research, 2024)
China's industrial policy to promote the development of the new energy vehicle industry has achieved remarkable success and has also been studied by many scholars. However, its fiscal policy has received more attention, and monetary policy is generally only mentioned together with fiscal policy, rarely studied separately. Therefore, this paper uses the Size Age (SA) index to measure the level of financial constraints that companies face and uses a panel regression model to analyze the impact of China's monetary policy on the financial constraints of new energy vehicle companies. This paper finds that traditional monetary policy tools represented by Loan Prime Rate (LPR) and several types of structural monetary policy tools have a significant effect on easing the financial constraints of China's new energy vehicle companies. Moreover, the two types of policies have formed a good synergy. Therefore, this paper recommends: In the current situation where China's monetary policy is loose while the US' monetary policy is tight, the current market interest rate level should be maintained or cautiously lowered; at the same time, the role of structural monetary policy tools should be played more actively and accurately to promote the development of China's new energy vehicle industry.